Is Indonesia Ready? A Legal and Policy Interrogation of Outcome-Based Academic Services for Accelerated Students with Disabilities - Rodiyah Rodiyah; Waspiah Waspiah; Bayangsari Wedhatami; Runjati Runjati (Journal of Indonesian Legal Studies, 2026)
This study critically examines Indonesia’s readiness to implement outcome-based education (OBE) in academic services for accelerated students with disabilities, situating the analysis within national legal frameworks and the global commitment to the Sustainable Development Goals (SDGs), particularly SDG 4 on inclusive and equitable quality education. Indonesia has formally recognized the right to inclusive education through key legal instruments, including Law No. 8 of 2016 on Persons with Disabilities and Law No. 12 of 2012 on Higher Education, which mandate accessibility and non-discrimination in educational provision. However, a persistent gap remains between these normative commitments and their practical implementation in higher education institutions. Employing a normative juridical method combined with conceptual and policy analysis, this research evaluates the extent to which existing regulations support the operationalization of OBE in inclusive academic services. The findings reveal that although Indonesian legal frameworks provide a general mandate for disability inclusion, they lack specific and enforceable standards for integrating OBE principles—such as measurable learning outcomes, adaptive assessment systems, and institutional accountability mechanisms—particularly within acceleration programs. This regulatory ambiguity contributes to fragmented implementation and limits the achievement of equitable educational outcomes, thereby constraining Indonesia’s progress toward SDG 4 targets. This article argues that Indonesia is not yet fully prepared to align its higher education system with both OBE principles and SDG commitments without substantial legal and policy reform. Strengthening regulatory coherence, embedding disability-sensitive outcome indicators, and enhancing institutional compliance mechanisms are essential to bridging the gap between rights and results. This study contributes to legal scholarship by linking national regulatory frameworks with global development agendas, offering pathways toward a more inclusive and globally competitive higher education system.